Nasal packing with Merocel in a glove finger after endoscopic endonasal reduction of medial blowout fracture. Issue 38 (24th September 2021) - Kim, Ji Hwan; Lee, Jun Yong; Lee, Joo-Yeon; Shim, Woo Sub; Wee, Jee Hye; Jung, Hahn Jin
Abstract : Abstract: After endoscopic endonasal reduction (EER) for medial blowout fracture (BOF), nasal packing may be necessary for sustaining the reduced orbital contents. This study aimed to introduce a new packing technique using Merocel in a glove finger. We retrospectively reviewed 131 patients with a mean age of 42.2 years (range, 13–80 years), who underwent EER for medial BOF, followed by a postoperative nasal packing of Merocel in a glove finger, between March 2016 and December 2019. Sex, age, side and cause of trauma, pre-operative diplopia and enophthalmos, duration from the occurrence of trauma to surgery, postoperative diplopia, enophthalmos, complications like sinusitis, and revision surgery were evaluated. The most common cause of injury was physical assault in 47 cases and a fall or slip event in 34. Pre-operatively 22 patients had diplopia and 1 patient had enophthalmos. Mean duration after trauma to the surgery was 13.2 days (range, 1–29 days). The mean operative time was 34.1 minutes (range, 10–70 minutes). Four weeks after operation, the nasal packing was removed at an outpatient clinic, with minimal pain, discomfort, and bleeding and no evidence of infection or inflammation. A computed tomography scan performed at 3 months postoperatively showed no re-bulging. The computed tomography image of 1 patient showed frontal sinus haziness; the patient had a headache and underwent endoscopic sinus surgery for symptomatic relief. Three patients had diplopia and 1 had enophthalmos at final follow-up. No other major postoperative complications were noted. Merocel in a glove finger packing technique proved itself to be safe and effective after EER for medial BOF.